Field Evaluation of Native B. thuringiensis Isolates Against Aphids (Aphis fabae) - GC, Ganga; Arjyal, Charu (Tribhuvan University Journal of Microbiology, 2020)
Objectives: The purpose of this study was to evaluate the aphicidal activity of native Bacillus thuringiensis (Bt) strains. Methods: Soil samples of Provinces 2 and 3 of Nepal were collected randomly for isolation of Bt by acetate selection method. Bt were identified by observing insecticidal crystal proteins (ICPs) by Commassie Brilliant Blue (CBB) staining technique. Aphicidal activity of 12 B. thuringiensis isolates was evaluated by two processes. The preliminary screening was done by spraying the suspension containing the spore and ICPs mixture in Phaseolus species heavily infested with black aphids (Aphis fabae) in fi elds. The second process (selective bioassay) was done by counting the number of aphids (nymphs, instar, winged, wingless) before and after spraying 5ml of suspension containing the spore and ICPs mixture on the leaf or on the beans pods surface infested by Aphids. The mortality percentage of Aphids after treatment was calculated on the 4th day, by counting the live aphids and the result was recorded. Results: Preliminary screening for aphicidal activity revealed that 4 isolates ML5(1), CW1(1), SN2(1) and MP2(1) producing spherical crystal protein, showed 100% mortality against nymphs, instar, winged and wingless Aphids. Isolates were effective in controlling the Aphid (Aphis fabae) within 4 days and the part of the plant that was sprayed becomes free of Aphids. Selective bioassay of native isolate MP3(3) was most effective in killing 95.83% of aphids followed by CW2(1), 85.71%, ML5(1), 77.34%, SN3(1), 72.72%, CW1(1), 70.21%. Conclusion: This study revealed that indigenous Bacillus thuringiensis of Terai region of Nepal are effective in controlling Aphids.